Analisis rugi kalor selama proses pemanasan pada semi-spherical plenum stainless steel 316 berdasarkan perubahan setting suhu pemanasan - Zavi Indasyach Moreno; Ronald Akbar; Almira Citra Amelia; Hilman Adrian; Jeff Michael Johanes; Putut Hery Setiawan; Hyundianto Arif Gunawan; Ragil Sukarno; Darwin Rio Budi Syaka; Mulya Juarsa (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Reactor core melting in a semi-spherical geometry has released heat during severe accidents in nuclear reactors, where the heat-dissipating characteristics need to be studied. So, the study aims to determine the temperature distribution phenomenon and the heat loss rate in stainless steel 316 semi-spherical. This study used a semi-spherical plenum to simulate nuclear reactor debris by experimental methods. Experiments were carried out using four temperature variations from 50oC, 100oC, 150oC, and 200oC. The measuring instrument used is a K-type thermocouple that has been installed at 14 predetermined points. Data taken are the process of increasing and decreasing the temperature in the semi-spherical plenum and the value of the heat loss rate. Based on the experimental results, it was found that the characteristics of the increase and decrease in temperature during the heating and cooling processes at each thermocouple point tended to be the same. Heat loss values that were obtained at temperatures of 50oC, 100oC, 150oC, and 200oC were 354.235 watts, 670.714 watts, 1442.303 watts, and 2064.727 watts. The value of the heat loss will increase in proportion to the size of the setting temperature. The heat loss rate value for all experiments exceeds 50%.